Insentif Pajak, Pengetahuan Perpajakan Dan Kepatuhan Wajib Pajak: Studi Empiris Dengan Terbitnya PMK Nomor 44/PMK.03/2020 - Paramita, Nadira Pradnya; Dwija Putri, I G A M Asri (E-Jurnal Akuntansi; Vol 34 No 8 (2024)DO - 10.24843/EJA.2024.v34.i08.p15, 2024)
This study is to determine the impact of taxpayer compliance on public sector corporate taxpayers in South Badung Regency according to PMK Number 44 PMK.03 / 2020 and tax knowledge during the Covid-19 pandemic. This research was conducted on MSMEs registered as taxpayers in South Badung Regency. The total sample taken using the proportional random sampling method with the Slovin technique was 100 MSME taxpayers registered in South Badung district. The analysis technique used was multiple linear regression analysis. . Based on the data that has been collected and the test results using multiple linear regression models, the following conclusions can be drawn: the impact of tax incentives has a positive effect on corporate taxpayer compliance in the SME industry in the southern part of Badung Regency. Taxpayer knowledge has a positive effect on corporate taxpayer compliance in the MSME environment of South Badung Regency Keywords: The Influence of Tax Incentives, Taxpayer Knowledge, Taxpayer Compliance.